2023
DOI: 10.1021/acs.bioconjchem.3c00174
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Lipid Nanoparticle Formulations: Immunological Safety and Efficiency Perspective

Abstract: Lipid nanoparticles (LNPs) have been recognized as efficient vehicles to transport a large variety of therapeutics. Currently in the spotlight as important constituents of the COVID-19 mRNA vaccines, LNPs play a significant role in protecting and transporting mRNA to cells. As one of their key constituents, polyethylene glycol (PEG)−lipid conjugates are important in defining LNP physicochemical characteristics and biological activity. PEGylation has proven particularly efficient in conferring longer systemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 219 publications
0
11
0
Order By: Relevance
“…As our surface modulation strategy relies on hydrophobic interactions between the cell membrane and the amphiphilic conjugate, the interaction is likely influenced by both PEG length and DS level of the lipid–PEG moiety in the HA backbone. Specifically, the length of PEG could regulate (1) internalization of materials into the cell, often observed with lower MW of PEG, and (2) inhibition of interaction between cells and materials with a higher MW of PEG. This phenomenon has been shown in various studies. For instance, previous research has demonstrated that approximately a half-permeability of PEG 1.5k into mesenchymal stem cells was obtained than the internalization level of PEG 0.6k .…”
Section: Resultsmentioning
confidence: 96%
“…As our surface modulation strategy relies on hydrophobic interactions between the cell membrane and the amphiphilic conjugate, the interaction is likely influenced by both PEG length and DS level of the lipid–PEG moiety in the HA backbone. Specifically, the length of PEG could regulate (1) internalization of materials into the cell, often observed with lower MW of PEG, and (2) inhibition of interaction between cells and materials with a higher MW of PEG. This phenomenon has been shown in various studies. For instance, previous research has demonstrated that approximately a half-permeability of PEG 1.5k into mesenchymal stem cells was obtained than the internalization level of PEG 0.6k .…”
Section: Resultsmentioning
confidence: 96%
“…72 In turn, copolymers based on PEG and OEG, as well as PEGlylated particles or dendrimers of various natures, are of great importance in biomedicine and other applications. [73][74][75][76][77] Therefore, in our work we wanted to demonstrate the possibility of introducing oligomeric ethylene oxide fragments (triethylene glycol monopropargyl ether (mTEG)) into the shell of a carbosilane dendrimer by azide-alkyne cycloaddition on a heterogeneous catalyst, which has also not been done previously.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…DMG-PEG 2000 and ALC-0159 are the PEGylated lipids used in Modernas elasomeran and Pfizer-BioNTechs tozinameran COVID-19 vaccines, respectively. 208…”
Section: Nanoparticlesmentioning
confidence: 99%